Damage Analysis of Elbow Fitting at Condenser Air Conditioning Cooling System - Hari Prastowo; Irfan Syarif Arief; Hamzah Fansyuri (Institut Teknologi Sepuluh Nopember, 2017)
Elbow fittings is one type of fitting on the piping installation that serves to change the flow direction. With the sudden flow of changes, it will affect the physical condition of the elbow. The flow changes in the elbow will result in changes of flow velocity that affect wall of elbow, the condition will cause erosion corrosion phenomenon. Erosion corrotion is a type of corrosion that uses a mechanical process through the relative movement of the flow and metal. Corrosion erosion can also be caused by impingment corrotion or very rapid flow movement. This study aims to determine the cause of damage elbow by using a CFD simulation and troubleshooting by adding a Vortex Generator or a installed disturber system in the pipeline installation and simulating it again. From the results of research conducted that elbow damage caused by high flow velocity that concerns the outer elbow. The addition of Vortex Generator is proven to be used to reduce excessive flow velocity on erosion-corroded parts. According to the results of the investigation the placement of the most efficient vortex generator if placed at a distance of 0.1 R from elbow inlet.